2010
DOI: 10.1117/12.845647
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring breast masses with ultrasound tomography in patients undergoing neoadjuvant chemotherapy

Abstract: The purpose of this study was to correlate changes in biomechanical properties of breast cancer lesions in response to neoadjuvant chemotherapy. Nine patients were examined repeatedly throughout their treatment, using an experimental prototype based on the principles of ultrasound tomography. The study was HIPAA compliant, approved by the Institutional Review Board, and performed after obtaining the requisite informed consent. Images of reflection, sound speed and attenuation, representing the entire volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This could potentially reduce the number of false-positive biopsies as well as the number of falsely down-staged lesions. Similarly to what has already been shown for US by Sannachi et al 50 and for SoS US by Lupinacci et al, 51 SoS-US could potentially be used as a fast and easy tool to predict the tumor response to chemotherapy. The current resolution is too low to make a conclusive statement on inner lesion structure.…”
Section: Discussionmentioning
confidence: 54%
“…This could potentially reduce the number of false-positive biopsies as well as the number of falsely down-staged lesions. Similarly to what has already been shown for US by Sannachi et al 50 and for SoS US by Lupinacci et al, 51 SoS-US could potentially be used as a fast and easy tool to predict the tumor response to chemotherapy. The current resolution is too low to make a conclusive statement on inner lesion structure.…”
Section: Discussionmentioning
confidence: 54%
“…This study builds on previous work that was based on lower-quality sound speed images reconstructed from a simpler algorithm (29). While the earlier study also demonstrated the ability to monitor changes in and V and VASS, it did not yield statistically significant differences between the complete and partial responders.…”
Section: Discussionmentioning
confidence: 73%
“…The images and data were collected during the period March 23, 2007 to June 17, 2011. An early UST prototype (27) of the SoftVue system (Delphinus Medical Technologies, Novi, MI) was used in the original data collection, which included 21 patients (29). The current study represents a new analysis of the data using a new high-resolution reconstruction algorithm (30).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…SoftVue was developed by Delphinus Medical Technologies (DMT), and is based on an early prototype [27][28][29][30][31][32][33] developed at the Karmanos Cancer Institute (KCI). The SoftVue imaging system was designed to provide enhanced performance relative to the prototype.…”
Section: Introductionmentioning
confidence: 99%